Balanchine in Paris - Balanchine, George; Braham, Myriam Ould; Ciaravola, Isabelle; Colin, Valéry; Delouche, Dominique 1931-; Denard, Michaël; Halle, Muriel; Lacarra, Lucía; Loudières, Monique; Markova, Alicia Dame 1910-2004; Moreau, Hervé; Pierre, Cyril; et al.
"Balanchine in Paris is the most recent film in the collection, Etoiles pour l'example, by the distinguished French film maker, Dominique Delouche. Throughout his life, the Russian-born choreographer, more usually associated with New York City Ballet which he founded with Lincoln Kirstein in 1934, kept close contact with France, the country where his first creations were staged and where he so nearly became the artistic director of the Paris Opera Ballet. He would even choose French perfumes for each of his ballerinas and always insisted upon having a French ballerina in his company. In his film, two of these almost legendary figures, Violette Verdy and Ghislaine Thesmar, are shown coaching younger dancers at the Palais Garnier in Paris the roles that they themselves were taught by the great master, for nearly 30 of his works, including ballets created especially for the company, or re-staged for the French dancers, form part of the repertory of the Paris Opera Ballet today. Indeed, the film opens with shots of Thesmar and Michael Denard interpreting the grand adage from the second movement of Le Palais de Cristal, created for the company in 1947, and now danced as Symphony in C, before superimposing shots of Isabelle Ciaravola and Hervé Moreau being coached in the same pas de deux by Ghislaine Thesmar herself."--Review by Patricia Boccadoro, http://www.culturekiosque.com
Title from resource description page (viewed Oct. 18, 2013)
Keywords: Ballet; Balanchine, George; Documentary films; Instructional films; Online media